Comparison of Haematological Values among Different Groups of Low Birth Weight Babies and Normal Birth Weight Babies - Ali, MA; Shahidullah, M; Hossain, MA; Ahmed, NU; Kawsar, CA (Mymensingh Medical Journal, 2008)
Mymensingh Med J. 2008 Jul;17(2):152-6.The abstract of this article is available on the PubMed website